Studies of human antiviral CD8+ lymphocytes using class I peptide tetramers. - Lechner, F; Cuero, A; Kantzanou, M; Klenerman, P (2001)
Understanding the interactions between a host and a pathogen relies crucially on quantitative measurements of immune responses. Until recently, measurements of the levels of cellular immune responses, i.e. those mediated by CD4+ and CD8+ T lymphocytes have depended largely on culture in vitro and subsequent measurement of specific functions (such as cytolysis). More recently, new technologies based around tetrameric class I peptide complexes (tetramers) have allowed immunologists to measure CD8+ T lymphocyte levels directly ex vivo and independently of function. Since CD8+ lymphocytes play a key role in a number of important human viral infections, these tools have yielded useful insights into the dynamics, phenotype and function of human antiviral lymphocyte populations. In this review we describe some of the basic aspects of the biology of virus-specific CD8+ lymphocytes, and the current methods available to detect them. The use of tetramers has, in just four years, transformed our understanding of the immune responses against HIV, HTLV-1, HBV, HCV, CMV and EBV, and holds promise in a number of areas where quantitative analysis of the antiviral response in terms of both number and function is critical.